The Formation and Evolution of S0 Galaxies - Garcia Bedregal, Alejandro Pablo (2007)
This thesis studies the origin of local S0 galaxies and their possible links to other morphological types. To address these issues, two different approaches have been adopted: a detailed study of the stellar populations of S0s in the Fornax Cluster and a study of the Tully-Fisher Relation (TFR) of local S0s in different environments.